A Patient with Non-Hodgkin's Lymphoma of the Spinal Region with Tuberculosis Spondylitis Infection: A Case Report - Helen Widiani; Losen Adnyana (PT Dexa Medica, 2025)
Primary non-Hodgkin’s lymphoma (NHL) of spinal origin is very rare, accounting for only 0.1% of all NHL, with spinal cord compression is the first symptom. Tuberculosis (TB) spondylitis is a chronic granulomatous inflammatory disease of thespine caused by Mycobacterium tuberculosis. Some patients will experience neurological deficits. If the M. tuberculosis bacterial infection affects the vertebral body, the resulting damage causes spinal instability and disruption of the surrounding structures. Patients can experience paraparesis or tetraparesis due to compression of the spinal cord. This disease has symptoms such as back pain, kyphosis, and constitutional syndrome. A case of a 75-year-old male patient with non-Hodgkin’s lymphoma diffuse large cell region spine stage IV ECOG 4, tuberculosis spondylitis on antituberculosis drugs special regimen intensive phase.